Critical Winter. - Pepi, Mike (Art in America, 2020)
The article offers information related to the impact of Artificial Intelligence on the art industry. It mentions about involvement of AI in art mentioned in the book "The Artist in the Machine: The World of AI-Powered Creativity" by Arthur I. Miller; and thousands of portrait photos from Flickr to create images of people who never existed mentioned in the book "Portraits of Imaginary People" by Michael Tyka.